Pengaruh Foktor-Faktor Total Quality Managemet Terhadap Peningkatan Mutu Pendidikan SMA Negeri di Surabaya - Anggia B.P, Feliks (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2017)
This study talks about the Effect of Total Quality Managemet Factors on Improving the Quality of Secondary School Education in Surabaya. The research population is all teachers of Senior High School who have worked for 5 years at least. A sample of 150 Teachers. Result of research: 1). From result of test "F" that variable = X1 = quality dimension; X2 = Focus on learners; X3 = Leadership; X4 = Sustainability Improvement and X5 = Human Resource Management simultaneously influence Educational Quality Improvement, this is supported by the value of R Square (RÂ²) of 0.752 and F = 9.589 with Sig = 0.001 <= 0.05. 2). From the result of t test (partial test), it can be concluded that from the 5 variables that have partial influence is the Variable The quality dimension has the effect of 20.1% to the improvement of the Quality of Education, and has the contribution value on the change of Education Quality improvement equal to = 4.1%. Variable X3 = Leadership has influence of 33.1% to the improvement of Education Quality, and has contribution value on change of Education Quality improvement = 11.0% with value of Sig 0.000 <= 0.05. The Continuous Improvement Variable has an influence of 18.4% on the improvement of Education Quality h, and has contribution value on the change of Education Quality improvement in Surabaya State High School equal to = 0.034% with value of sig 0.000 <= 0.05. Keywords: Total Quality Managemet, Quality Improvement of Education.